Highly sensitive biosensor based on aptamer and hybridization chain reaction for detection of cadmium ions. (17th February 2022) - Xu, Mingming; Peng, Yu; Yang, Hualin; Zhou, Yu
Abstract: In this work, a highly sensitive biosensor for detecting cadmium ions (Cd 2+ ) was developed based on a Cd 2+ ‐specific DNA aptamer and a hybridization chain reaction (HCR). The Cd 2+ aptamer (named S0) was used to recognize Cd 2+ and trigger the HCR. Without Cd 2+, S0 initiated the HCR to form long nicked dsDNA structures to quench the fluorescence. Then, Cd 2+ could bind with S0 to block HCR to recover fluorescence. This biosensor had high sensitivity with a detection limit of 0.36 nM and a linear range from 0 to 10 nM. Moreover, it showed a satisfactory selectivity and recovery rates. Abstract : A highly sensitive Cd 2+ biosensor was developed through Cd 2+ binding to a Cd 2+ aptamer to inhibit the HCR process. An aptamer was used to initiate the HCR to form long nicked dsDNA structures to quench the fluorescence of FAM. When Cd 2+ was added, it could bind with the aptamer to block HCR to recover fluorescence.